Influence of Flashback Narrations In the Literary Works of William Golding: Exploring the Conflict between Rationalism and Faith in William Golding's Free Fall (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Golding uses the flashback technique of Pincher Martin more extensivelyin his next novel, Free Fall (1959).Unlike his first three novels, FreeFall is told with a first person narrator, an artist named SamuelMountjoy. The novel takes as a model Dante's La Vita Nuova, a collection of love poems interspersed withDante's own commentary on the poems. Golding uses the character Mountjoy tocomment on the conflict between rationalism and faith.